O vlogi in pomenu avstrijskih uradnikov v okupirani Bosni in Hercegovini na primeru življenja in dela sodnika Augustina Oblaka (1867–1935) - Vodopivec, Barbara (Studia Historica Slovenica, 2023)
Based on literature, archival sources from the Archives of the Republic of Serbia and family archives, as well as interviews with relatives, historians and legal experts, the article describes activities of the judge Augustin Oblak (1875, Vrhnika – 1935, Ljubljana) during his work as a civil servant in Bosnia and Herzegovina between 1895 and 1934. His life and work are placed in the context of the occupation and annexation of Bosnia and Herzegovina, the establishment of a new administrative and legal system, the activities of secret student associations and the repressive reaction of the authorities. At the same time, the text traces the social conditions of the ethnically and religiously diverse environment of the time and devotes particular attention to Banja Luka, where Oblak and his family lived for the longest time. The article is based on the methods of historiography and biographical research and draws on the contexts of microhistory and cultural transfer.
Keywords: Annexation of Bosnia and Herzegovina to the Austro-Hungarian Monarchy (1908); Avstro-Ogrska; civil servants; history; Javni uslužbenci; Oblak, Augustin; okupacija Bosne in Hercegovine; Priključitev Bosne in Hercegovine Avstro-Ogrski (1908); secret student organizations; slovenski sodniki; tajna dijaška društva; Zgodovina